Fuzzy‐dependent switched fault‐tolerant tracking control for permanent magnet synchronous generator‐based wind energy conversion system - Kuppusamy, Subramanian; Joo, Young Hoon (International journal of adaptive control and signal processing, 2023)
Summary This article investigates the switched fault‐tolerant tracking control techniques for a permanent magnet synchronous generator (PMSG)‐based variable‐speed wind energy conversion system (WECS) subject to actuator faults. To do this, a Takagi‐Sugeno fuzzy model is exploited to delineate the nonlinear WECS composed of a PMSG and wind turbine. By using the switching technique and Lyapunov functional including membership function information, fault‐tolerant tracking control is proposed to effectively track the optimal trajectory of PMSG‐based WECS states with known and unknown actuator faults. Also, the stabilization conditions are derived in the form of linear matrix inequality to determine the control gains, which assures the maximum power output and enhance the system performance. Meanwhile, the H∞$$ H_{∞ } $$ performance index is presented with membership function, for attenuating the load torque disturbance of WECS. Finally, the superiority and benefit of presented method are validated by numerical simulations.